Synthesis and structures of divalent Co, Ni, Zn and Cd complexes of mixed dichalcogen and dipnictogen ligands with corrosion inhibition properties: experimental and computational studies. Issue 69 (18th November 2020) - Yusuf, Tunde L.; Quadri, Taiwo W.; Tolufashe, Gideon F.; Olasunkanmi, Lukman O.; Ebenso, Eno E.; van Zyl, Werner E.
Abstract : The structural and corrosion inhibition properties of four different transition-metal complexes of heteroleptic S-donor atom dithiophosphonate and N-donor atom phenanthroline ligands are reported. Abstract : The structural and corrosion inhibition properties of four different transition-metal complexes of heteroleptic S-donor atom dithiophosphonate and N-donor atom phenanthroline ligands are reported. Full structural characterization of the Co, Ni, Zn and Cd complexes was achieved with the aid of single-crystal X-ray crystallography. Structural elucidation revealed the formation of a 4-coordinate Zn(ii ) complex, and 6-coordinate Ni(ii ) and Cd(ii ), as well as a novel dithiophosphonato Co(ii ) complex. The ability of the complexes with this ligand type to act as inhibitors of mild steel corrosion in 1 M HCl solution is reported for the first time. Corrosion inhibition potentials of the complexes were assessed using potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), and density functional theory (DFT). The open circuit potential (OCP) time profile showed the system achieved a steady-state potential before the first 600 s after submerging the working electrode in the corrosive medium. The studied metal complexes are good inhibitors of mild steel corrosion in 1 M HCl and were found to retard the corrosion rate by forming an adsorbed pseudocapacitive film on the steel surface. The order of inhibition efficiencies was in the order Ni (94.14%) > Cd (92.28%) > Zn (91.14%) > Co (72.53%).